IMPROVING MANAGEMENT OF CROSS-FUNCTIONAL PROCESSES AS A WAY OF ACHIEVING COMPETITIVE ADVANTAGE IN CULTURE INSTITUTION - E. Belyi; E. Khodzhayan (Вестник университета, 2016)
The functioning of culture institution is characterized by market conditions. General patterns of competitive interaction between stakeholders are analyzed. Example of the museum shows that the conquest of competitive advantage in culture institutions is achieved by improving the management of cross-functional processes. The method of identifying processes which are realizing competitive strategy.